Sandpile model on subdivided wheels Wn,l - Raza, Zahid; Tariq, Saleha; Rahim, M.Tariq (Utilitas Mathematica, 2017)
The sandpile model using chip-firing game is defined on finite connected undirected graph. The combinatorial structure of the subdivided wheels Wn,i for even I is described in this paper. The family of subdivided wheels Wn,i is defined by taking a simple wheel graph Wn with n rim vertices and then adding I extra vertices between each of the rim edges. It has (l + l)n + 1 number of vertices and size (l + 2)n. © 2017 Utilitas Mathematica Publishing Inc.. All rights reserved.